Assessment of factors limiting technological capabilities crimping conical die blanks from thick-walled pipes - V. A. Konovalov; Yu. A. Chugunova (Омский научный вестник)
The results of an experimental study of the formation of thickwalled hollow products compressed with conical matrices are presented. The influence of the characteristics of the tool and the size of the blanks on the technological capabilities of crimping is established. The quantitative evaluation is made in the form of graphs, which make it possible to predict more accurately the final configuration and dimensions of the stamped product.